(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2007)
In this article, the results of the investigation of separate stages in reproductive process of the rare species Paeonia tenuifolia L. that grown short in quantity and has protective status are given. Peculiarities of fertilization, of endosperm and embryo development are found out. Calendar terms of this process flowing in the conditions of Crimea are given. This work is illustrated by microphotographs.